LANDASAN PEDAGOGIK PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Anwar Taufik Rakhmat; Tatang Hidayat (Taklim : Jurnal Pendidikan Agama Islam, 2022)
AbstractIslamic religious education is very important to be studied by students and students. On the other hand, Islamic Religious Education in schools and colleges is one of the subjects and courses that must be given to students and students. The purpose of this research is to analyze the pedagogical foundation of Islamic religious education in schools. The pedagogical foundation for the importance of Islamic Religious Education in schools includes theoretical and philosophical studies of humans in relation to Islamic Religious Education. Some formulations of pedagogical foundations in Islamic Religious Education in schools are humans as educational creatures who are able to be educated and educated, lifelong education, education as a human need and humans as religious creatures.Keywords : Pedagogical, Islamic Religious Education, SchoolAbstrakPendidikan Agama Islam sangat penting dipelajari oleh siswa dan mahasiswa. Di sisi lain, Pendidikan Agama Islam di sekolah dan perguruan tinggi merupakan salah satu mata pelajaran dan mata kuliah yang wajib diberikan kepada siswa dan mahasiswa. Tujuan penelitian ini untuk menganalisis landasan pedagogik Pendidikan Agama Islam di sekolah. Penelitian ini menggunakan pendekatan kualitatif dan metode studi literatur. Berdasarkan hasil pembahasan, landasan pedagogik terhadap pentingnya Pendidikan Agama Islam di sekolah meliputi kajian teoritis dan filosofis tentang manusia dalam kaitannya Pendidikan Agama Islam. Beberapa rumusan landasan pedagogik dalam Pendidikan Agama Islam di sekolah adalah manusia sebagai makhluk pendidikan yang mampu dididik dan mendidik, pendidikan sepanjang hayat, pendidikan sebagai kebutuhan manusia dan manusia sebagai makhluk religious.Kata Kunci : Pedagogik, Pendidikan Agama Islam, Sekolah